Effect of Compost Fertilizer and Nasa Liquid Organic Fertilizer on the Growth and Yield of Cucumber (Cucumis sativus L.) Misano F1 Variety - Emiliana Lidya; Noor Jannah, Abdul Rahmi (Universitas 17 Agustus 1945 Samarinda, 2018)
The research objective were to study the effect of compost fertilizer and Nasa liquid organic fertilizer (POC Nasa) and its interaction on the growth and yield of cucumber and also to find the proper dosage of compost fertilizer and POC Nasa concentration for obtaining the best growth and yield of cucumber.The research used Completely Randomized Design (CRD) in 4 x 4 Factorial Experiment and three replications. The factor was the dosage of compost fertilizer (K) consisting of 4 levels : no compost fertilizer application (k0), 48 g polybag-1(k1), 64 g polybag-1 (k2); and 80g polybag-1(k3). The second factor was the concentration of POC Nasa (D) consisting 4 levels : no POC Nasa application (d0), 1 ml l-1water (d1), 2 ml l-1water (d2), and 3 ml l-1water (d3).The results showed that: (1) the compost fertilizer treatment affected significantly on the weight of one fruit and the weight of fruit per plant, it affected very significantly on the plant lenght at age 15 and 30 days after planting, and fruit diameter, but it did not affect significantly on the number of fruit per plant. The best production was produced at 48 g polybag-1 (k1) treatment of 3,77 kg plant-1, while the least one was produced at the 80 g polybag-1 (k3) treatment of 3,06 kg plant-1; (2)the POC Nasa treatment affected significantly on the weight of one fruit; and it affected very significanly on the plant lenght at age 30 days after planting and fruit diameter, but it did not affect significantly on the plant lenght at age 15 days after planting, number of fruit per plant, and fruit weight per plant; and (3) the interaction treatment between compost fertilizer and POC Nasa affected significantly on the weight of one fruit and affected very significantly on the fruit diameter, but did not affect significantly on the plant lenght at age 15 and 30 after planting, the number of fruit and fruit weight per plant.